Minimally invasive endodontics: a new era for pulpotomy in mature permanent teeth - Nebu Philip (14779318) (2022)
Emerging clinical and histologic evidence is challenging the long-established dogma that root canal treatment (RCTx) is the only therapeutic option for preservation of vital mature permanent teeth diagnosed with irreversible pulpitis or carious pulp exposure. Vital pulp therapy procedures like pulpotomy are not only technically simpler and more economical, but also afford patients a host of other benefits over conventional RCTx. This narrative review provides an update on the contemporary understanding of pulp pathophysiology and defence mechanisms, the proposed new diagnostic terminologies for pulpal inflammation, and how the biological characteristics of hydrophilic calcium silicate cements have enabled consistent successful outcomes for pulpotomy-treated mature teeth. The paper also details the evidence base from clinical trials and systematic reviews conducted over the past decade and outlines the practical treatment considerations for pulpotomy in mature permanent teeth. Other Information Published in: British Dental Journal License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41415-022-5316-1